THE IMPACT OF E-SERVICE QUALITY ON CUSTOMER LOYALTY WITH CUSTOMER SATISFACTION AS MEDIATING VARIABLE (CASE STUDY OF TRAVELOKA IN PONTIANAK) - Konstantia, Stella (Jurnal Manajemen Update, 2018)
This study aimed to investigate the direct and indirect impact of electronic service quality towards customer satisfaction and customer loyalty on Traveloka in Pontianak. The respondents are Pontianak citizen who ever access to Traveloka website and did transaction in Traveloka for the last 6 months. Primary data was gathered using online questionnaire on 100 respondents ofTraveloka’s customers in Pontianak. The data was analyzed based on multiple linear regression analysis using SPSS version 22.0. Data processing results shows that the electronic service quality had a significant impact on customer satisfaction and customer loyalty. The electronic service quality includes Reliability, Website Design, Responsiveness, and Privacy. The findings of this study also proved that Customer Satisfaction mediated the relation between Electronic Service Quality and Customer Loyalty.Keywords: electronic service quality, customer satisfaction, customer loyaltyTHE IMPACT OF E-SERVICE QUALITY ON CUSTOMER LOYALTY WITH CUSTOMER SATISFACTION AS MEDIATING VARIABLE (CASE STUDY OF TRAVELOKA IN PONTIANAK)